Politics of Folklore in Croatia - Grgurinović, Ivona; Marković, Jelena (2012)
The idea of two cultures, the culture of the people and the culture of the gentry (Radić – the founder of Croatian ethnology), the little and the great tradition (Redfield), the culture of dominant and subordinate groups (Gramsci, Cirese) etc., has been present since the establishment of ethnology and folklore research as scientific disciplines. Ethnology and folklore research have constituted as sciences of “little” traditions, of subordinated groups and their cultural practices, which by no means form a monolithic, homogenous unity. Researchers of folklore have become aware of the dialectical relationship between high and low cultures through criticism pointed toward their object of research, which has frequently been construed through the eyes of the “high” culture. Researchers of folklore have criticized the scientific interest for the picturesque and unusual, necessarily past (and old), aesthetically interesting and representative cultural practices. Despite this epistemological turn, the atavistic feel of the discipline's name and its object remains. This atavism results partly from folkoristics' (and ethnology’s, in some of its approaches) political striving to preserve in the present something not entirely of the present. This is why folklore has constantly been under the attack of political instrumentalization and under the pressure of official ideologies, especially during the times of political crises and the establishment of new political, economic and ideological systems, which has happened several times in recent Croatian history. Folklore has proven to be very politically potent in the educational system for selecting traditions serving official ideologies, although it has been long known that folklore could not be taught as part of the official education, because the knowledge transferred in the educational system stands in opposition to the explicit and implicit conceptions which generate folklore. Political, social, economic and cultural changes in Croatia since 1945 have influenced the revalorization of the old and the “invention” of new folklore practices. The aim of this paper is to provide an analysis of the dialectical relationship between two conceptions of world and life in Croatia: the popular, traditional, “low”, unofficial, heterogeneous one, and the official, selective one, striving to present homogenous, stabile, representative and socially mobilizing symbols of identity which have their roots in the spontaneous communication in small groups (cf. Ben-Amos) and everyday culture of rural areas. The paper will primarily focus on the (re)presentation of traditional culture in educational curricula, such as the regulation of the relationship toward traditional beliefs present in oral legends after 1945, when a new form of relationship between the Church and the state were established ; the relationship toward the folklore from the War of National Liberation until 1990 and after, etc.
Projekt MZOS
Projekt MZOS
ENG